2013
DOI: 10.1093/annhyg/met071
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Working Position on Trunk Posture and Exertion for Routine Nursing Tasks: An Experimental Study

Abstract: Objectives:To examine the influence of the two following factors on the proportion of time that nurses spend in a forward-bending trunk posture: (i) the bed height during basic care activities at the bedside and (ii) the work method during basic care activities in the bathroom. A further aim was to examine the connection between the proportion of time spent in a forward-bending posture and the perceived exertion.Methods:Twelve nurses in a geriatric nursing home each performed a standardized care routine at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The angular accuracy of the sensors is better than 1° in quasi-static conditions [ 20 , 22 , 23 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The angular accuracy of the sensors is better than 1° in quasi-static conditions [ 20 , 22 , 23 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This coincides with the video analyses, in which we found that in 55% of bedside care situations, nurses only partially raised the bed, if at all. Although proper adjustment of the resident’s bed resulted in better working postures and less strain on the body (Freitag et al , 2014), nurses argued that this procedure was time consuming (Petzäll et al , 2001). However, it takes an average of 53–59 s to raise a bed from knee to hip height (Freitag et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding work situations were then analysed interactively, and alternative ergonomic solutions were discussed. The aforementioned laboratory study not only showed that raising the bed height and using a stool in the bathroom led to a reduction in unfavourable body postures but also that when participants adhered to these ergonomic principles they felt that their work was less stressful (Freitag et al , 2014). These findings were taken into account in practical implementation of ergonomic ways of working at the residents’ bedsides and in the bathroom (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pressure loads, awkward body postures are common in elderly care [ 12 ]. These can be reduced considerably by adopting ergonomic measures such as raising bed heights [ 13 ].…”
Section: Introductionmentioning
confidence: 99%